TRPC Channels in Proteinuric Kidney Diseases - Gentzon Hall (Cells, 2019)
Over a decade ago, mutations in the gene encoding TRPC6 (transient receptor potential cation channel, subfamily C, member 6) were linked to development of familial forms of nephrosis. Since this discovery, TRPC6 has been implicated in the pathophysiology of non-genetic forms of kidney disease including focal segmental glomerulosclerosis (FSGS), diabetic nephropathy, immune-mediated kidney diseases, and renal fibrosis. On the basis of these findings, TRPC6 has become an important target for the development of therapeutic agents to treat diverse kidney diseases. Although TRPC6 has been a major focus for drug discovery, more recent studies suggest that other TRPC family members play a role in the pathogenesis of glomerular disease processes and chronic kidney disease (CKD). This review highlights the data implicating TRPC6 and other TRPC family members in both genetic and non-genetic forms of kidney disease, focusing on TRPC3, TRPC5, and TRPC6 in a cell type (glomerular podocytes) that plays a key role in proteinuric kidney diseases.